Factors Affecting Budget Absorption with the Support of Islamic-Based Leadership as a Moderating Variable in the Government of Southeast Aceh Regency - Dicky Zulkarnaen (El-Qish: Journal of Islamic Economics, 2024)
The aim of this research is to test and analyze the effect of budget participation and clarity of budget targets on budget absorption moderated by leadership support. The approach used in this research is an associative approach. The population in this study was all regional apparatus organizations (OPD) in Southeast Aceh district, totaling 33 OPDs. The sample in this study was taken from 3 people from each regional apparatus organization (OPD), consisting of the head of department or secretary, authorized budget user and head of program subdivision so that the number of respondents was 99 people. Data collection techniques in this research used documentation studies and questionnaires. The data analysis technique in this research uses a quantitative approach using statistical analysis using Auter Model Analysis, Inner Model Analysis and Hypothesis Testing. Data processing in this research uses the PLS (Partial Least Square) software program. The results of this research prove that budget participation and clarity of budget targets have a significant effect on budget absorption, leadership support moderates the influence of budget participation and clarity of budget targets on budget absorption in Southeast Aceh Regency